I'm using given the following definition of the Fourier transform: $$\hat{f}(k)=F[f]=\int_{\mathbb{R}} f(x)e^{-ikx} \, dx $$

I'm then asked to find the transform of the function defined by $$\begin{cases} e^{-x} & x>0 \\ 0 & x<0\end{cases}$$

I have done this and got $$F[f]=\frac{1}{1+ik}$$

I'm then asked to use the inversion formula $$F^{-1}[\hat{f}]=\frac{1}{2\pi}\int_{\mathbb{R}} \hat{f}(k)e^{ikx} \, dk $$ to compute $$\int_{0}^{\infty}\frac{\cos kx+k\sin kx}{1+k^2} \, dk$$

How do I do this part?


We have the Fourier Transform pair

$$f(x)=e^{-x}u(x)\leftrightarrow F(k)=\frac{1}{1+ik}$$

Denote the unit step function by $u(x)$. Then, we see that

$$\begin{align} e^{-x}u(x)&=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{e^{-ikx}}{1+ik}\,dk\\\\ &=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{e^{-ikx}}{1+ik}\frac{1-ik}{1-ik}\,dk\\\\ &=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{e^{-ikx}(1-ik)}{1+k^2}\,dk\\\\ &=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{(\cos(kx)-i\sin(kx))(1-ik)}{1+k^2}\,dk\\\\ &=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{\cos(kx)+k\sin(kx)}{1+k^2}\,dk-i\frac{1}{2\pi}\underbrace{\int_{-\infty}^\infty\frac{k\cos(kx)+\sin(kx)}{1+k^2}}_{=0\,\,\text{since we have an odd integrand}}\,dk\\\\ &=\frac{1}{2\pi}\int_{-\infty}^\infty\frac{\cos(kx)+k\sin(kx)}{1+k^2}\,dk \end{align}$$

Therefore, we find that

$$\int_{-\infty}^\infty\frac{\cos(kx)+k\sin(kx)}{1+k^2}\,dk=2\pi e^{-x}u(x)$$


Couple of hints:

$e^{ik} = \cos k + i\sin k$

and $F[f]$ can be re-written

$\displaystyle \frac {1-ik}{1+k^2}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.